KESEPAKATAN SEMU SECARA OTENTIK PADA PERJANJIAN UTANG PIUTANG OLEH KREDITUR - Deny Haspada (Scientia Regendi, 2019)
The making of an agreement deed is not justified for unilateral interests, but must contain the interests of each party, therefore the engagement must be made based on the agreement of the parties making it. The agreement is stated in writing, it can be made under the hand in the sense that it is only made by the parties, it can also be made authentically in front of a notary, but what is clear is that the contents of the agreement contained must be understood by each party and there is no other interpretation of what has been published so that in the future if there is a legal consequence it is clear the legal consequences that must be borne by the party who broke the promise (default), but if the default is due to a violation by taking advantage of the conditions so that a false agreement occurs, which the partner does not want, that includes the form defective will, with the abuse of the beneficiary of this condition, the agreement can be canceled. If the parties make an agreement according to their conscience, there is no coercion, no cheating to extract illegal profits, then there will be no use of the conditions in the form of the Pseudo Agreement, so that if the deed is made authentically by way of a pseudo agreement, if the deed is disputed, it must be null and void by law or canceled through a Judge's Decision at the District Court because from the beginning the deeds were not drawn up according to procedure, namely the two deeds were already flawed due to fake agreement manipulation between the parties making the agreement.